(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Hypovitaminosis D (<20 ng/mL) is thought to increase insulin resistance and meta-inflammation contributing to the pathogenesis of diabetes mellitus (DM). Correcting vitamin D deficiency in people with prediabetes might halt its progression to DM. The aim of this study was to examine the effect of vitamin D supplementation on insulin resistance, glycemic status, and inflammation in prediabetic adults with vitamin D deficiency. This doubleblind randomized placebo-controlled trial was done among 27 newly detected prediabetic adults with hypovitaminosis D randomly assigned to 60,000 IU of vitamin D weekly for eight weeks followed by monthly for the next four months or placebo along with lifestyle modification in both groups [vitamin D (n= 14) vs. Placebo (n=13). They were comparable in terms of sex, age and borlymass index. Glycemic status, fasting plasma glucose (FPG) and Hemoglobin A1C (HbA1C), insulin resistance (homeostasis model assessment of insulin resistance (HOMA-IR) and inflammatory marker high sensitivity C reactive protein (hs-CRP) were measured at baseline and after six months of intervention. Vitamin D levels (ng/mL) increased in both groups from baseline (vitamin D vs. placebo: 12.2±5.9 vs. 3.9±3.5, mean±SD). FPG (mmol/L) significantly decreased in the Vitamin D group (before vs. after: 5.9±0.6 vs. 5.5±0.7, P=0.016, mean±SD), whereas HbA1C (%) and hs- CRP (mg/L) significantly increased in the placebo group (before vs. after- HbA1C: 5.8±0.3 vs. 6.0±0.4, P<0.001; hs-CRP: 5.0±4.4 vs. 5.6±4.9, P=0.039, mean±SD). Percent changes in glycemic status, HOMA-IR, and hs-CRP were statistically similar between the groups. Our study failed to demonstrate the positive effects of vitamin D supplementation on reducing glucose, insulin resistance, or inflammatory marker in prediabetic adult patients with hypovitaminosis D. BSMMU J 2022; 15(3): 167-174